2019
DOI: 10.1038/s41598-019-38955-3
|View full text |Cite
|
Sign up to set email alerts
|

Tailing miniSOG: structural bases of the complex photophysics of a flavin-binding singlet oxygen photosensitizing protein

Abstract: miniSOG is the first flavin-binding protein that has been developed with the specific aim of serving as a genetically-encodable light-induced source of singlet oxygen (1O2). We have determined its 1.17 Å resolution structure, which has allowed us to investigate its mechanism of photosensitization using an integrated approach combining spectroscopic and structural methods. Our results provide a structural framework to explain the ability of miniSOG to produce 1O2 as a competition between oxygen- and protein que… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 43 publications
3
73
1
Order By: Relevance
“…A higher number of oxidative modifications of amino acids detected in our work in comparison with a very recent paper by Torra et al 29 can be attributed to the differences in the solution irradiation (wavelength, power, etc.) and partially also to the higher sensitivity and resolution obtained by our LC-MS/MS analysis on FT-ICR MS and combination of proteomics approaches directed at localization of the modification sites.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…A higher number of oxidative modifications of amino acids detected in our work in comparison with a very recent paper by Torra et al 29 can be attributed to the differences in the solution irradiation (wavelength, power, etc.) and partially also to the higher sensitivity and resolution obtained by our LC-MS/MS analysis on FT-ICR MS and combination of proteomics approaches directed at localization of the modification sites.…”
Section: Discussioncontrasting
confidence: 67%
“…Our approach truly analyzes all protein states present in the sample and, in addition, the top-down analysis allows the identification of the first-hit residues. In contrast, Torra et al 29 identified the oxidized residues in the crystal structure, hence the possibility that they observed just the crystallization-capable population cannot be excluded.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other than CCK2R sensitization through SALPC photodynamic action, we also examined photodynamic CCK2R modulation with the genetically encoded protein photosensitizer miniSOG. miniSOG (106 residues) with a noncovalently bound fluorophore flavin mononucleotide (FMN) is a protein photosensitizer with sufficient 1 O 2 quantum yield (≥0.03) [53,54]. Other than generating 1 O 2 , miniSOG, upon excitation with blue light (448 nm), also emits green (500 nm) fluorescence [55,56] and therefore can be used as a fluorescent tag for protein subcellular localization and protein-protein interactions [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Crystallographic studies showed an increase in rigidity of the chromophore's environment compared to wild-type LOV2 suggesting that oxygen diffusion can occur properly. [84] When irradiated with blue light, miniSOG fluoresces and generates both superoxide anion (and its derivatives) and singlet oxygen ( 1 O 2 ) through type I and II mechanisms. [85,86] This dual function allowed the imaging of MiniSOG by correlative light and electron microscopy (CLEM) in Caenorhabditis elegans and mice synaptic cells.…”
Section: Actuatorsmentioning
confidence: 99%